A RhABF2/Ferritin module affects rose (Rosa hybrida) petal dehydration tolerance and senescence by modulating iron levels. (30th November 2017) - Liu, Jitao; Fan, Youwei; Zou, Jing; Fang, Yiqun; Wang, Linghao; Wang, Meng; Jiang, Xinqiang; Liu, Yiqing; Gao, Junping; Zhang, Changqing
Summary: Plants often develop the capacity to tolerate moderate and reversible environmental stresses, such as drought, and to re‐establish normal development once the stress has been removed. An example of this phenomenon is provided by cut rose ( Rosa hybrida ) flowers, which experience typical reversible dehydration stresses during post‐harvest handling after harvesting at the bud stages. The molecular mechanisms involved in rose flower dehydration tolerance are not known, however. Here, we characterized a dehydration‐ and abscisic acid (ABA)‐induced ferritin gene ( RhFer1 ). Dehydration‐induced free ferrous iron (Fe 2+ ) is preferentially sequestered by RhFer1 and not transported outside of the petal cells, to restrict oxidative stresses during dehydration. Free Fe 2+ accumulation resulted in more serious oxidative stresses and the induction of genes encoding antioxidant enzyme in RhFer1‐ silenced petals, and poorer dehydration tolerance was observed compared with tobacco rattle virus (TRV) controls. We also determined that RhABF2, an AREB/ABF transcription factor involved in the ABA signaling pathway, can activate RhFer1 expression by directly binding to its promoter. The silencing of RhABF2 decreased dehydration tolerance and disrupted Fe homeostasis in rose petals during dehydration, as did the silencing of RhFer1 . Although both RhFer1 and Fe transporter genes are induced during flower natural senescence in plants, the silencing of RhABF2 or RhFer1 accelerates the petal senescence processes. These results suggest that the regulatory module RhABF2/RhFer1 contributes to the maintenance of Fe levels and enhances dehydration tolerance through the action of RhFer1 locally sequestering free Fe 2+ under dehydration conditions, and plays synergistic roles with transporter genes during flower senescence. Significance Statement: In the present work, we find that ferritin Fe‐buffering is required for dehydration tolerance of cut roses under reversible stress conditions; the regulatory module RhABF2/RhFer1 affects Fe levels to confer the tolerance in rose flowers by RhFer1 locally sequestering free Fe2+ under dehydration conditions; the RhABF2/RhFer1 module via the interaction of ABA with ethylene plays synergistic roles in the regulation of Fe levels with transporter genes during flower natural senescence.